A Grey Area Phenomena: A Survival of Informal Cross Border Trade at Sebatik Island, Malaysia - Fauzie Sarjono; Kartini Aboo Talib@Khalid; Chan, Rachel Suet Kay; Noor Syakirah Zakaria; Amrullah Maraining; Syahruddin Awang Ahmad; Zainuddin Baco; Siti Nurbayu Yusof; Aishah Meri (Science Research Society, 2021)
This article unravels the concept of the grey area phenomenon which is getting more specific and intense. The complexity of borders remains a core point regarding boundaries, informal cross border trade, and threats to national security. This article focuses on investigating the survival of informal economic activities in Sebatik Island. This study uses a qualitative approach in the form of field observations and interviews as the main source of primary data of this writing. The results suggest that the grey area phenomenon concentrated in Sebatik Island creates benefits and detriment related to both countries’ survival.